Information Security Techniques for Open Distributed Computing Systems Based on the Application Technology of “Hot” Reservation Servers - I. I. Zenzin (Безопасность информационных технологий, 2010)
Here we present some examples how to use the technologies of «hot» reservation servers constructed on the basis of UNIX-like operating systems. The main principles how the system of «hot» reservation servers is working are described.